2022
DOI: 10.1021/acs.accounts.1c00796
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Complex Mixtures by Chemosensing NMR Using para-Hydrogen-Induced Hyperpolarization

Abstract: Conspectus Nuclear magnetic resonance (NMR) is a powerful technique for chemical analysis. The use of NMR to investigate dilute analytes in complex systems is, however, hampered by its relatively low sensitivity. An additional obstacle is represented by the NMR signal overlap. Because solutes in a complex mixture are usually not isotopically labeled, NMR studies are often limited to 1 H measurements, which, because of the modest dispersion of the 1 H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Recently, PHIP has been extended to amino acids, which can have far-reaching implications for metabolism studies (Figure ). The discovery of SABRE and SABRE-SHEATH (shield enables alignment transfer to heteronuclei) as non-hydrogenation routes to achieve nuclear spin polarization has enabled high nuclear polarization of both proton and heteronuclear spins in a broad range of metabolites and other compounds and does not require unsaturated target molecules. An excellent review on the application of these methods that can now selectively detect and quantify analytes down to nanomolar concentrations has been reported recently . Further, using this approach, the analysis of urine metabolites was recently reported, which avoids the need for solid-phase extraction (SPE) and replaces it with a minimal sample manipulation that retains the majority of urinary metabolome.…”
Section: New Methods To Increase Sensitivity and Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PHIP has been extended to amino acids, which can have far-reaching implications for metabolism studies (Figure ). The discovery of SABRE and SABRE-SHEATH (shield enables alignment transfer to heteronuclei) as non-hydrogenation routes to achieve nuclear spin polarization has enabled high nuclear polarization of both proton and heteronuclear spins in a broad range of metabolites and other compounds and does not require unsaturated target molecules. An excellent review on the application of these methods that can now selectively detect and quantify analytes down to nanomolar concentrations has been reported recently . Further, using this approach, the analysis of urine metabolites was recently reported, which avoids the need for solid-phase extraction (SPE) and replaces it with a minimal sample manipulation that retains the majority of urinary metabolome.…”
Section: New Methods To Increase Sensitivity and Speedmentioning
confidence: 99%
“…11−16 An excellent review on the application of these methods that can now selectively detect and quantify analytes down to nanomolar concentrations has been reported recently. 17 Further, using this approach, the analysis of urine metabolites was recently reported, 18 which avoids the need for solid-phase extraction (SPE) and replaces it with a minimal sample manipulation that retains the majority of urinary metabolome. A persistent challenge, however, is that the hyperpolarization approach does not boost the signal intensity evenly across all molecules in a mixture, which makes the determination of concentrations more difficult.…”
mentioning
confidence: 99%
“…112 The potential of SABRE for mixture analysis has been explored by Tessari and co-workers, who showed that the method can be applied to complex mixtures of molecules with concentrations in the micromolar range, provided that an appropriate co-substrate is also added to the mixture. 113,114 They also showed that the signal intensity changes linearly with concentration in that regime. With a standard-addition method, they were able to quantify several analytes in an artificial mixture.…”
Section: Parahydrogen-based Hyperpolarisationmentioning
confidence: 98%
“…In another study, Dey et al presented an untargeted NMR-based metabolomic workflow based on dissolution DNP thereby enabling hyperpolarised 13 C metabolomics of plant extracts at natural abundance [8]. Despite of these and several other [9,10] extremely encouraging results, typical liquid-state NMR experiments employing d-DNP-or parahydrogen-based hyperpolarisation will, most likely, have a limited applicability in metabolomics research due the very specific and demanding sample preparation/setup requirements, e.g., harsh hyperpolarisation conditions and/or long polarisation times in combination with the occasional need for expensive additional instrumentation, which render biocompatible and automated high-throughput NMR measurements rather difficult.…”
Section: Introductionmentioning
confidence: 99%